Safety by Design : Human-Centered Approaches to AI, Automation, and Remote Operations - Frøy Birte Bjørneseth; Stig Ole Johnsen; Ole Andreas Alsos; Vidar Hepsø; Gunhild Birgitte Sætren (CRC Press, 2026)
Safety-critical systems with more digitalization, automation, and AI require integration of human factors to ensure safety, efficiency, and meaningful human control. Across sectors such as aviation, maritime, energy, transportation, and remote operations, accident investigations repeatedly show that failures often stem not from technology alone but from inadequate scoping, poor human-centered design, alarm overload, fragmented automation, and organizational conditions that leave operators unprepared during critical situations. Disasters such as the Boeing 737 MAX accidents demonstrate how safety can be compromised when humans and systems are misaligned, while successful recoveries (such as the US Airways Flight 1549 landing on the Hudson River) show the vital role of design-supported human performance in demanding conditions.Safety by Design: Human-Centered Approaches to AI, Automation, and Remote Operations explores the relationship between human capabilities, organizational readiness, and complex technical systems. It offers best practices for designing safety-critical systems that integrate human factors from concept to operation. The book introduces Meaningful Human Control, a framework ensuring humans retain authority, awareness, and intervention ability, aligning with emerging EU AI regulations. Readers will learn practical methods to design systems with usability, transparency, and oversight, alongside insights into automation, accident analysis, and supporting operators under stress. These principles help create safer, more resilient, and trustworthy systems.This book has been written for human factors students and specialists, system designers, engineers, safety professionals, regulators, and project managers working on safety-critical applications involving automation, AI, or remote operations.The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a creative commons (CC BY) 4.0 license.